Short selling pressure and corporate social responsibility performance - LU, Louise Yi (Institutional Knowledge at Singapore Management University, 2016)
Using Regulation SHO as a natural experiment, we show that managers respond to apositive exogenous shock of short selling pressure by enhancing corporate socialresponsibility (CSR) performance. The positive effect of short selling on CSR is mainlydriven by improvements in stakeholder CSR, rather than third party CSR; and byimprovements in CSR strengths, rather than reductions in CSR concerns. We further findthat the effect is more pronounced for firms that locate in environments where CSR isemphasized by their stakeholders. Moreover, we find that managers are more likely toissue CSR reports that convey information about firms’ CSR activities to the publicduring the implementation of Regulation SHO period. Overall, our evidence is consistentwith our conjecture that managers use CSR strategically to deter short sellers by creatinga positive image of the firm.